2022
DOI: 10.1532/hsf.4325
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Melatonin for Delirium in Elderly Acute Heart Failure Patients: A Randomized, Single-Center, Double-Blind, and Placebo-Controlled Trial

Abstract: Background: Delirium is a common, life-threatening, typical clinical syndrome with the main clinical manifestations of temporary organic mental disorder without specific drug treatment. The aim of the study was to explore the benefits of melatonin for the treatment of delirium after acute heart failure in elderly patients. Methods: This was a randomized, double-blind, and placebo-controlled trial. This study enrolled patients aged more than 60 years after acute heart failure. A computer-generated randomization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 7 publications
0
12
0
2
Order By: Relevance
“…Six trials exclusively included surgical patients admitted to the ICU. Of these trials, 1 trial [16] included elderly patients with acute heart failure after surgery and did not explicitly report the type of surgery. In the remaining 5 trials, patients underwent liver resection, [24] elective on-pump coronary artery bypass graft surgery, [19,25] elective pulmonary thromboendarterectomy surgery, [20] and percutaneous transluminal coronary intervention surgery.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six trials exclusively included surgical patients admitted to the ICU. Of these trials, 1 trial [16] included elderly patients with acute heart failure after surgery and did not explicitly report the type of surgery. In the remaining 5 trials, patients underwent liver resection, [24] elective on-pump coronary artery bypass graft surgery, [19,25] elective pulmonary thromboendarterectomy surgery, [20] and percutaneous transluminal coronary intervention surgery.…”
Section: Resultsmentioning
confidence: 99%
“…In our older patients aged ≥ 60 years, 5 trials with 956 patients provided data. Of these, 3 trials [16,18,25] included only older patients aged > 60 years, 1 trial [19] conducted by Jaiswal et al reported the incidence of delirium in patients aged ≥ 65 years, and the remaining 1 [19] by Zadeh et al reported the incidence of delirium in patients aged > 70 years. Melatonin reduced the occurrence of delirium in older patients (RR, 0.69; 95% CI: 0.57–0.83; I 2 = 0%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations